Morphological and Mechanical Properties of the Quadriceps Femoris Muscle-Tendon Unit From Adolescence to Adulthood: Effects of Age and Athletic Training - Charcharis, Georgios; Mersmann, Falk; Bohm, Sebastian; Arampatzis, Adamantios (Frontiers in Physiology, 2019)
The combined effects of mechanical loading and maturation during adolescence are still not well understood. The purpose of the study was to investigate the development of the quadriceps femoris muscle-tendon unit from early adolescence (EA), late adolescence (LA) to young adulthood (YA), and examine how it is influenced by athletic training in a cross-sectional design. Forty-one male athletes and forty male non-athletes from three different age groups (EA: 12–14 years, n = 29; LA: 16–18 years, n = 27; and YA: 20–35 years, n = 25) participated in the present study. Maximum strength of the knee extensor muscles, architecture of the vastus lateralis (VL) muscle and patellar tendon stiffness were examined using dynamometry, motion capture, electromyography, and ultrasonography. Muscle strength and tendon stiffness significantly increased (p < 0.001) from EA to LA without any further alterations (p > 0.05) from LA to YA. Athletes compared to non-athletes showed significantly greater (p < 0.001) absolute muscle strength (EA: 3.52 ± 0.75 vs. 3.20 ± 0.42 Nm/kg; LA: 4.47 ± 0.61 vs. 3.83 ± 0.56 Nm/kg; and YA: 4.61 ± 0.55 vs. 3.60 ± 0.53), tendon stiffness (EA: 990 ± 317 vs. 814 ± 299 N/mm; LA: 1266 ± 275 vs. 1110 ± 255 N/mm; and YA: 1487 ± 354 vs. 1257 ± 328), and VL thickness (EA: 19.7 ± 3.2 vs. 16.2 ± 3.4 mm; LA: 23.0 ± 4.2 vs. 20.1 ± 3.3 mm; and YA: 25.5 ± 4.2 vs. 23.9 ± 3.9 mm). Athletes were more likely to reach strain magnitudes higher than 9% strain compared to non-athlete controls (EA: 28 vs. 15%; LA: 46 vs. 16%; and YA: 66 vs. 33%) indicating an increased mechanical demand for the tendon. Although the properties of the quadriceps femoris muscle-tendon unit are enhanced by athletic training, their development from early-adolescence to adulthood remain similar in athletes and non-athletes with the major alterations between early and LA. However, both age and athletic training was associated with a higher prevalence of imbalances within the muscle-tendon unit and a resultant increased mechanical demand for the patellar tendon.